A utilização de jogos lúdicos na aprendizagem matemática com alunos do 6º ano do ensino fundamental em uma escola municipal da zona rural - Dantas, Kelson Paiva (Brasil, 2024)
At first, mathematics is seen by students as a monotonous discipline, a constant complaint among students, since the focus of the learning process is on students, in this sense, for this to happen, it is necessary to awaken their interest. Through, academic experiences provide me, to research on this topic. The use of ludic games in mathematical learning: with students of the 6th year of elementary school in a municipal school in the rural area. In this sense, the need to facilitate learning with basic operations in the sixth year of elementary school led me to use games as an alternative for learning these contents. Despite this, this research has the general objective of analyzing the pedagogical action of ludic games as teaching strategies in the four mathematical operations, identifying ludic games with an educational function, there is a pedagogical purpose and its importance in teaching/learning mathematics, in the same way, verifying the use of ludic games in learning the four operations. In this sense, in order to reach the objective, a field research was carried out with an of a qualitative approach. In this way, this research was applied to students of the 6th year of Elementary School of a Municipal School in the municipality of Coari - AM located in the rural area.